Ce-Cokodok Al-Rizqi / Muhammad Khairul Ariffin Mohd Nor ... [et al.] - Mohd Nor, Muhammad Khairul Ariffin; Kamaruzzaman, Muhammad Aminuddin; Mahmud Rasid, Nur A'in Qistina; Shalan, Nurhaziqah; Sahlan, Nurizzatul Saleha (2017)
Cekodok is a traditional Malays fritter snack in Brunei, Malaysia and Indonesia that is made from flour and fried. There are many varieties of cekodok such as mixing it with banana, onion, and prawns. Our company name Ce-Cokodok Al-Rizqi and our shop that is Ce-Cokodok Al-Rizqi is located at Lot 2, Ground Floor, Kluang Parade, Jalan Sentul, 86000 Kluang, Johor, Malaysia. We provide the best cekodok that people, family and friends can enjoy it while it hot just like "Out from the oven". For Ce-Cokodok Al-Rizqi, we focusing on separating cekodok to three types which is original cekodok, chocolate chip cekodok, and corn cekodok. We added a variety content or fillings inside the cekodok such as chocolate, strawberry and blueberry. Our Ce-Cokodok Al-Rizqi product also provide a delivery services so that people can buy it via hotline at the specific area around Kluang. We also include flyers and made a social media account to promote our product even better in the area outside of Kluang johor. This way, Malaysian people will knows our product better and can even reach international such as Singapore and Indonesia. We, Ce-Cokodok Al-Rizqi, saw the opportunity that this business. has the potential of success that we have provided. This is because our product still focusing on the traditional Malays fritters so that customers can still taste the originality of the food that Malaysian people proud of. For people who want to eat for a snack, Ce-Cokodok Al-Rizqi is the best way to eat either individually or hanging out with family and friends.